2019
DOI: 10.1021/acs.jproteome.8b00911
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Human Plasma Proteome Profile on Adaptation to High-Altitude Hypobaric Hypoxia

Abstract: For individuals migrating to or residing permanently in high-altitude regions, environmental hypobaric hypoxia is a primary challenge that induces several physiological or pathological responses. It is well documented that human beings adapt to hypobaric hypoxia via some protective mechanisms, such as erythropoiesis and overproduction of hemoglobin; however, little is known on the alterations of plasma proteome profiles in accommodation to highaltitude hypobaric hypoxia. In the present study, we investigated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 56 publications
(113 reference statements)
0
27
0
Order By: Relevance
“…Healthy HA participants (healthy HA group) and HAPC patients (HAPC group) with no visits to LA regions in at least 1 years prior to this study were recruited at People's Hospital of Aba Tibetan and Qiang Autonomous Prefecture, which is located in Aba Tibetan and Qiang Autonomous Prefecture, Sichuan, with an average altitude >3000 m. Healthy LA subjects (LA group) who were reported no visits to HA regions in at least 1 years prior to this study were enrolled from Meishan Blood Center, Sichuan (<500 m). As we reported previously [14,15], the diagnosis of HAPC was HGB ≥ 190 g/L for female or ≥ 210 g/L for male which based on the criteria defined at the 2004 Qinghai International High Altitude Medicine Conference, and it also accompanied by the following clinical manifestations: headache, dizziness, tinnitus, fatigue, insomnia, cyanosis, conjunctival congestion, dyspnea, palpitations, and venous dilatation. Inclusion criteria were that all the recruited participants were ≥18 years old and unrelated.…”
Section: Sample Selectionmentioning
confidence: 83%
See 2 more Smart Citations
“…Healthy HA participants (healthy HA group) and HAPC patients (HAPC group) with no visits to LA regions in at least 1 years prior to this study were recruited at People's Hospital of Aba Tibetan and Qiang Autonomous Prefecture, which is located in Aba Tibetan and Qiang Autonomous Prefecture, Sichuan, with an average altitude >3000 m. Healthy LA subjects (LA group) who were reported no visits to HA regions in at least 1 years prior to this study were enrolled from Meishan Blood Center, Sichuan (<500 m). As we reported previously [14,15], the diagnosis of HAPC was HGB ≥ 190 g/L for female or ≥ 210 g/L for male which based on the criteria defined at the 2004 Qinghai International High Altitude Medicine Conference, and it also accompanied by the following clinical manifestations: headache, dizziness, tinnitus, fatigue, insomnia, cyanosis, conjunctival congestion, dyspnea, palpitations, and venous dilatation. Inclusion criteria were that all the recruited participants were ≥18 years old and unrelated.…”
Section: Sample Selectionmentioning
confidence: 83%
“…In our previous study, we found that coagulation factors (F)II, FV, FVII, FVIII, FIX, FX, FXI, FXII were significantly lower in HA than in low altitude (LA) blood donors while anticoagulant factors (protein C, protein S and antithrombin III (AT-III)) showed no significant changes between LA and HA blood donors [25]. Our previous proteomic studies also displayed that plasma proteomics profiles significantly altered between high altitude polycythemia (HAPC) patients and HA healthy controls [14], and between HA and LA participants [15]. Moreover, we found that, in HA participants, prothrombin time (PT) and activated partial thromboplastin time (APTT) negatively correlated with hemoglobin (HGB) concentrations [26].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…These tags permit multiplexing of several samples per LC-MS run, commonly 4, 6, 8, or 10 samples, but more are possible 91 . To learn more about the use of isobaric labeling for plasma proteomics, see review by Moulder et al, 92 and recent applications 37,93,94 . Multiplexing methods compensate for throughput concerns associated with large sample numbers and some plasma processing workflows (e.g., fractionation), enabling the combination of several samples 95,96 .…”
Section: Quantification Workflowsmentioning
confidence: 99%
“…Previous evidences revealed that high altitude has stress detrimental influences on the functions of several cells due to free-radical damage sojourners, and mountaineers frequently experience different degrees of organ damage during high-mountain journeys. In recent years, a number of studies have revealed changes in the levels of molecules of organ damage caused by HH (Wang et al 2019 ; Woods et al 2017 ; Du et al 2019 ). Previous studies have demonstrated that HH can induce an array of pathological reactions, including biochemical, molecular, and genomic alterations, most of which has focused on a certain tissue, such as the brain, heart, or lung.…”
Section: Introductionmentioning
confidence: 99%